2003
DOI: 10.1007/s00280-003-0685-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of normal and tumor tissue uptake of MAG-CPT, a polymer-bound prodrug of camptothecin, in patients undergoing elective surgery for colorectal carcinoma

Abstract: Delivery of CPT to the target tumor tissue is achievable by means of the MAG-CPT polymer-bound delivery system, with the equilibrium between plasma and tumor tissue concentrations of released CPT being established within 24 h after dosing. However, preferential retention of MAG-bound or released CPT in the tumor relative to normal tissue or plasma was not detected during the 7 days after dosing. The methods employed in our study could be of use in making "go/no-go" decisions on further development of anticance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…The linkage of camptothecin to the polymer carrier was designed for pHcatalysed esterolytic cleavage, in contrast to the proteasebased release of doxorubicin employed here, making it hard to compare the pharmacology of the two drug conjugates. Nevertheless, a further study administered PNU166148 to patients with colorectal cancer prior to tumour resection, and found disappointingly low levels of the drug within resected tumour tissue (24). This suggests that the EPR effect does not operate very effectively in clinical colorectal cancer, and this may contribute to the lack of activity seen against colorectal cancer in the present study as well (although the minor response in colorectal cancer observed in the phase I study should not be completely overlooked).…”
Section: Discussioncontrasting
confidence: 44%
“…The linkage of camptothecin to the polymer carrier was designed for pHcatalysed esterolytic cleavage, in contrast to the proteasebased release of doxorubicin employed here, making it hard to compare the pharmacology of the two drug conjugates. Nevertheless, a further study administered PNU166148 to patients with colorectal cancer prior to tumour resection, and found disappointingly low levels of the drug within resected tumour tissue (24). This suggests that the EPR effect does not operate very effectively in clinical colorectal cancer, and this may contribute to the lack of activity seen against colorectal cancer in the present study as well (although the minor response in colorectal cancer observed in the phase I study should not be completely overlooked).…”
Section: Discussioncontrasting
confidence: 44%
“…Gamma camera imaging has shown some evidence to support EPR174-mediated tumour localisation in patients (Vasey et al 1999). However, when colorectal cancer patients were given HPMA copolymer-camptothecin (MAG-CPT) 24 h before surgical removal of the tumour, the levels of conjugate measured in tumour tissue did not show preferential localisation compared to normal tissue (Sarapa et al 2003). Further studies are needed in the clinical setting to clarify the clinical significance of the EPR effect in human tumours of different tissue origin and the extent of targeting at different stages of tumour development (primary, metastatic, postsurgery, etc.).…”
Section: Polymer-drug Conjugates: Rationale For Designmentioning
confidence: 99%
“…They demonstrated delivery of CPT to the target tumour tissue and found the equilibrium between plasma and tumour tissue concentrations of released CPT being established within 24 h after dosing. No evidence for selective delivery or retention of MAG-CPT or preferential release of free CPT in tumour tissue was found (Sarapa et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…An interesting approach to investigate CPT accumulation in human tumour tissue was recently published by Sarapa et al Normal and tumour tissue uptake of MAG-CPT was assessed in patients undergoing elective surgery for colorectal carcinoma (Sarapa et al, 2003). Patients received a single dose of 60 mg m À2 of MAG-CPT either 24 h, 3 days, or 7 days prior to surgery.…”
Section: Discussionmentioning
confidence: 99%